Airbnb impacts on host communities in a tourism destination: an exploratory study of stakeholder perspectives in Queenstown, New Zealand. Issue 5 (4th May 2022) - Cheng, Mingming; Houge Mackenzie, Susan; Degarege, Gebeyaw Ambelu
Abstract: Airbnb's disruptive impacts on tourism destinations have been well acknowledged but systematic examination is still lacking. This study investigates these impacts on host communities from the perspectives of tourism destination stakeholders including Airbnb hosts, traditional accommodation providers, local residents and policy makers in Queenstown, New Zealand. Underpinned by social representation theory, the results of fourteen semi-structured interviews confirm the complexity of Airbnb growth, which is characterised by multiple and conflicting interests, and potential paradoxes in destination management policies. This research highlights the advantage of using multiple stakeholder perspectives by providing a more holistic and critical understanding of Airbnb's impacts. It offers a starting point to inform the on-going debate regarding sustainable tourism development in destinations with globally disruptive entities.